Adoption of electronic health records and barriers. Issue 5 (1st January 2016) - Palabindala, Venkataraman; Pamarthy, Amaleswari; Jonnalagadda, Nageshwar Reddy
Abstract : Electronic health records (EHR) are not a new idea in the U.S. medical system, but surprisingly there has been very slow adoption of fully integrated EHR systems in practice in both primary care settings and within hospitals. For those who have invested in EHR, physicians report high levels of satisfaction and confidence in the reliability of their system. There is also consensus that EHR can improve patient care, promote safe practice, and enhance communication between patients and multiple providers, reducing the risk of error. As EHR implementation continues in hospitals, administrative and physician leadership must actively investigate all of the potential risks for medical error, system failure, and legal responsibility before moving forward. Ensuring that physicians are aware of their responsibilities in relation to their charting practices and the depth of information available within an EHR system is crucial for minimizing the risk of malpractice and lawsuit. Hospitals must commit to regular system upgrading and corresponding training for all users to reduce the risk of error and adverse events.